Patient characteristics and outcomes associated with adherence to the low PEEP/FIO2 table for acute respiratory distress syndrome - Kay Choong See (Nature Portfolio, 2021)
Abstract It remains uncertain how best to set positive end-expiratory pressure (PEEP) for mechanically ventilated patients with the acute respiratory distress syndrome (ARDS). Among patients on low tidal volume ventilation (LTVV), we investigated if further adherence to the low PEEP/FIO2 (inspired oxygen fraction) table would be associated with better survival compared to nonadherence. Patients with ARDS, admitted directly from the Emergency Department to our 20-bed Medical Intensive Care Unit (ICU) from August 2016 to July 2017, were retrospectively studied. To determine adherence to the low PEEP/FIO2 table, PEEP and FIO2 12 h after ICU admission were used, to reflect ventilator adjustments by ICU clinicians after initial stabilization. Logistic regression was used to analyze hospital mortality as an outcome with adherence to the low PEEP/FIO2 as the key independent variable, adjusted for age, APACHE II score, initial P/F ratio and initial systolic blood pressure. 138 patients with ARDS were analysed. Overall adherence to the low PEEP/FIO2 table was 75.4%. Among patients on LTVV, nonadherence to the low PEEP/FIO2 table was associated with increased mortality compared to adherence (adjusted odds ratio 4.10, 95% confidence interval 1.68–9.99, P = 0.002). Patient characteristics at baseline were not associated with adherence to the low PEEP/FIO2 table.